Does sodium phosphate enema use cause electrolyte disorder? Sodium-phosphate enema poisoning - Tomar Güneysu, Songül; Güleryüz , Okşan Derinöz; Karakaş , Nazmi Mutlu; Çolak , Özlem (Journal of Surgery and Medicine, 2024)
Constipation is one of the most common symptoms in childhood. Sodium-phosphate enemas are frequently preferred for the treatment of constipation and bowel cleansing. We present a case of a 5-year-old boy who presented to the Pediatric Emergency Department with complaints of constipation, abdominal pain, abdominal distension and vomiting; had been constipated for about two years and had poor nutrition, and received a full dose of CT enema® twice in the last 12 hours before admission to the hospital. Upon arrival at the Pediatric Emergency Department, the patient was given a pediatric fleet enema because he had dense stools according to radiographic evidence. Poisoning due to Sodium-phosphate enema was considered due to severe hyperphosphatemia and hypocalcemia in the laboratory evaluation. Rapid intravenous hydration and 1 mL/kg calcium gluconate intravenous infusion were started. Electrolytes returned to the normal range at the 14th hour of follow-up without the need for additional treatment. This case is presented to emphasize that due to the widespread use of sodium-phosphate enemas in the treatment of chronic constipation, these enemas can cause phosphate poisoning even when used in healthy patients at therapeutic doses.